Politics of Local Occultism: - Achmad Fawaid (Kawalu: Journal of Local Culture, 2016)
Abstract As a global occult practice, Tarot has been practiced by local people, including Javanese practitioners, and it is perhaps that a study of localization is necessary to determine how strongly influential Javanese belief system has been upon Tarot practitioners, or how Javanese Tarot practitioners have adopted and modified Javanese esoteric and occult practices into Tarot. My thesis is that localizing Tarot could be possible in terms of adaptation, acculturation, indigenization, or—in some extents—hybridization in Javanese society, either in the levels of superficial, practice, or values. By using ethnography as method of research, this study has resulted in two major findings: (1) Javanese Tarot practitioners have negotiated themselves in the cultic milieu they live in by localizing their alias, communities, Tarot reading strategies, Tarot decks, and their personal preference to gather in candi, and (2) Tarot practice in Java has closely been related to some Javanese belief systems, such as rasa and kahanan, and it makes them consciously or unconsciously practice Javanism in their daily activity of Tarot with different levels. However, these have implications and challenges they should deal with: cultural ambivalence, a cultural implication that they can’t be free from it, because as much as they play Western Tarot, they are still Javanese. This ambivalence also indicates an inseparable concept of globalization as dynamic one in the term of ‘localizing’. The idea of localizing Tarot makes it possible to be a global phenomena in which local Javanese belief system embedded into Javanese Tarot practice became a part of global network. The involvement of Javanese practitioners in e-commerce or international market suggests a juncture between particular occult practices and global ones to celebrate the cultural hybridity within Tarot. Keywords: Occult, Tarot, Javanism